Pengaruh Rasio Solvabilitas, Sales Growth Dan Total Asset Turnover Terhadap Pertumbuhan Laba - Desi Rahmawati; Dirvi Surya Abbas; Djenny Sasmita (Moneter : Jurnal Ekonomi dan Keuangan, 2024)
The purpose of this study was to determine the effect of solvency ratios, sales growth and total asset turnover on profit growth in Property and Real Estate Sub-Sector Companies listed on the Indonesia Stock Exchange (IDX). The sampling technique used purposive sampling technique. Based on the predetermined criteria obtained 14 companies. The type of data used is secondary data obtained from the Indonesia Stock Exchange website. The analytical method used is panel data regression analysis. The results showed that sales growth had a significant positive effect on profit growth, the solvency ratio and total asset turnover had no effect on profit growth .